The Phenomenon Of Peer Intimacy Who Is Married (Study Of Employees In The Education Department And Environment Culture Of Bengkulu Province) - Elesmi, Elesmi; Narti , Sri; Dhianti , Martha Heriniazwi (Social Sciences Journal, 2024)
This research was conducted to find out how the process of intimacy between co-workers occurs within the Bengkulu Province Education and Culture Service. This research uses descriptive qualitative methods. This research uses data collection techniques through in-depth interviews, observation and documentation. The technique for determining research informants uses purposive sampling using Altman Taylor's social penetration theory. The research results show that there is a phenomenon of intimate closeness between colleagues at the Bengkulu Province Education and Culture Service. This intimate closeness phenomenon occurs through 5 stages, namely the initial stage (surface contact), they know each other because they work in the same agency and spend time from 08.00-16.00, the exploration stage (exploratory affective exchange) they express each other's feelings intensely communicating on Whatsapp, commitment (affective exchange) they share trust and confidence and have an agreement not to contact outside office hours and always give female informants money, intimacy (self-disclosure) reveal personal information to each other and they have checked in at hotels and the stable stage of the relationship understands and they continue to carry out this relationship, supporting each other.